Comparative histomorphological study of endometrium in mares. (3rd January 2018) - Herrera, M.; Herrera, J. M.; Cantatore, S.; Aguilar, J.; Felipe, A.; Fumuso, E.
Summary: Uterine acute post‐breeding inflammation is a physiological tissue response to the entry of exogenous elements, with persistent endometritis being the main pathology responsible for subfertility in the mare ( Equus ferus caballus; Linnaeus, 1758). Mares can be classified as susceptible or resistant to endometritis according to their ability to remove intrauterine fluid within 48 hr after experimental inoculation. Endometrial biopsy is a technique that is commonly used to establish the degree of lesions that can affect the fertility of the mare. Endometrial histomorphometry is an objective and highly precise diagnostic method. The aim of this study was to compare, during oestrus, the endometrial histomorphometry of mares previously classified as susceptible (SM) or resistant (RM) to endometritis. Endometrial biopsies from 24 mares at the oestrus phase of the cycle were obtained. For the histomorphometric analysis, samples were histologically processed and subjected to routine Haematoxylin–Eosin staining. For the evaluation, the variables were considered as follows: 1‐Height of the lining and glandular epithelia (Lining SM = 15.9 μm vs. RM = 13.3 μm; Glandular SM = 15.0 μm vs. RM = 13.0 μm); 2‐Perpendicular diameters of endometrial glands (SM = 51.3 μm vs. RM = 44.8 μm); 3‐Number of endometrial glands per field (SM = 24.8 glands/field vs. RM = 20.5 glands/field). The results from this study suggest the existence of a relationship between the studied characteristics and the susceptibility/resistance to post‐breeding endometritis in mares. Thus, increased epithelial height, greater glandular density and greater development of the glands during oestrus would be related to a higher susceptibility to endometritis.